Factors associated with illegal motorcycle street racing and help-seeking intention - Wong, L.P. (2012)
The study aimed to identify the factors associated with street racing among the illegal motorcycle racers in Malaysia also known as the Mat Rempit, and their help-seeking intention. A total of 2,022 Mat Rempit were surveyed. The findings support the notion that experience-seeking, prestige-seeking, excitement-seeking, self-satisfaction, underestimate risk, and social influence were factors influencing illegal motorcycle street racing. The overall intention to seek help was extremely low. The majority (77.9) reported that they would solve the problem themselves and 75.5 thought that illegal street racing is not big deal and would go away in time. Participants with neither (OR 0.41; 95 CI 0.27-0.62) or at least one parent who is strict (OR 0.52; 95 0.37-0.73) were less likely to have high help-seeking intention than those with both parents who are strict. Study indicates a need for family-centered intervention to curb illegal street racing.